Hypoxia manipulating infiltrating T cells in solid tumor with respect to CD5 expression: Hypoxia reduces CD5 expression on T cells (Indian Journal of Experimental Biology (IJEB), 2025)
Reduced levels of oxygen in the microenvironment, defined by the term hypoxia, is a feature of the growing solid tumor. The hypoxic tumor microenvironment (TME) modulates the tumor-infiltrating lymphocytes (TILs), such as T cells, favoring tumor growth and survival. This mini-review emphasizes how hypoxia affects infiltrating CD8+ cytotoxic T cells and regulatory T cells (Tregs) within the TME. CD5, a T cell marker expressed by TIL and Tregs, is a negative regulator of T cell receptor (TCR) signaling. We propose two mechanisms of loss of TIL function in TME: firstly, reduction in the CD5 expression on TIL followed by activation-induced cell death (AICD). Here, our findings showed hypoxia-inducible factor-1a (HIF-1α) binding to the promoter of a non-conventional human endogenous retrovirus (HERV) derived alternate mRNA transcript of CD5. This results in reduced surface and increased intracellular expression of CD5 protein, a phenotype that is quite common in leukemic T cells, particularly in acute T cell lymphoblastic leukemia. Secondly, hypoxia attracts Treg cells, characterized by high CD5 levels, further suppressing TIL function. This minireview highlights an interplay between hypoxia, HIF-1α, and CD5 and provides insights into tumor immune evasion and inefficacy of TILs.